O jogo da imitação: uma análise da proteção do design de calçados à luz dos fundamentos, incentivos e limites dos desenhos industriais - Jade Vinagre e Lima (2021)
This work aims to analyze the protection given by design patents regime, evaluating its effects in women’s fashion footwear industry in Brazil. This investigation verifies the rule validity by its effectiveness and efficiency, analyzing the economic and juridical foundations of design patents that justify limiting the free access of consumer to creation, as well as imposing restraints on competition and enterprise liberties. The study was developed by gathering and examining data regarding shoes design registration and violation cases in Brazil; by an economic analysis of design patent law; and by describing fashion phenomena and its innovative process and the footwear industry characteristics. Through the economic analysis of a patent design infringement case, it was evaluated whether the protection of shoe design would be justified even if the infringement did not cause damage to innovator's goodwill and, thus, prevented the main goal of Design Patent Law of fostering innovation. This initial hypothesis was partially refuted by verifying that the economic use of the protected design would necessarily cause damage to the right holder, a result of the exploitation of his artificially protected market. On the other hand, it was concluded that reaching an efficient balance between the promotion of innovation and the well-being resulted of non-competitors’ copycats would require granting the non-rival agent access to creation. Therefore, a legislative change was suggested, proposing the removal of injunction measures if the infringer does not compete with the owner and if there is a compensatory measure to cover the damages caused.